Systematic Review: Penerapan Kecerdasan Buatan (AI) Dalam Pembelajaran IPA Meningkatkan Pemahaman Konsep dan Literasi Sains - Hasanah, Kamaliatul (Edukimbiosis: Jurnal Pendidikan IPA, 2025)
Science learning in schools is still largely focused on theoretical delivery and rote memorization, giving students limited opportunities to develop a deep and contextual understanding of scientific concepts. The advancement of Artificial Intelligence (AI) technology offers great potential to transform science learning into a more interactive, personalized, and meaningful process. This article employs the Systematic Literature Review (SLR) method by critically analyzing ten scientific journals published between 2021 and 2025 that discuss the application of AI in science education. The review process includes identification, selection, and analysis of research objectives, methodological designs, participant characteristics, and main findings. The results indicate that the integration of AI in science learning enhances conceptual understanding through adaptive learning features, visualization of abstract concepts, and automatic feedback. Moreover, AI-based learning strengthens students’ scientific literacy by providing learning experiences based on data exploration and independent scientific problem-solving. Several studies combine AI with inquiry-based and project-based learning models, resulting in significant improvements in critical thinking and scientific reasoning skills.